The Causes and Complications of Urinary Retention in Adult Males Managed at Pakistan Institute of Medical Sciences Islamabad Pakistan - Shahid Siraj, Amjad Saleem, Raza Ul Hassan, Ajmal Khan, Iftikhar Ahmad, Raja Naeem, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: urinary retention is characterized as body inability to empty the bladder completely by voluntary micturition. The UR is highly observed in the male adult. But the limited and sufficient knowledge is present about its causes and associated complication. Objective: It is most common urological emergency in hospitals. The study aimed to evaluate the causes and associated complications of urinary retention. Material and Methods: This prospective hospital based study was conducted on 176 patients visited the emergency department of Pakistan Institute of Medical Sciences Islamabad over a period of 06 months. The review board and ethical committee of the hospital approved the study. Informed consent was taken from all patients included in study. A brief history and examination was done to establish the diagnosis. Urinary retention was relived either by per urethral or supra-pubic cathrterization followed by detailed history, examination and investigations. The urine sample of each patient was taken for urinalysis. Baseline investigations were done on every patients. Depending on the clinical impression the investigations were individualized. The results were retrieved from the collected data. The data was statistically analyzed by using SPSS software. Results: 176 patients were recruited during this research time. The patients mean age was 58.81±17.36SD. The maximum number of patients encountered in age group of 55-74years. Most common cause of urinary retention was enlarge prostate 67.04%, followed by urethral stricture 18.75% and impacted urethral/Urinary bladder stone 14.20%. Acute urinary retention was diagnosed in 62.50% while 37.50% were diagnosed as chronic urinary retention. The 65.34% patients were treated with per urethral catheterization and 34.66% were treated with supra-pubic catheterization. In 62.50% patients no complication were observed while in other 19.88% were diagnosed with urinary tract infection and 17.62% with the renal insufficiency. Conclusion: Urinary retention is common in adult patients. Enlarge prostate was the one of the main cause of urinary retention. The most common type of retention was acute urinary retention. Complications were mostly associated with chronic urinary retention. Keywords: Urinary retention, Complications, adult male, Enlarge Prostate and acute urinary retention